2016
DOI: 10.1159/000448209
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Clinical Efficacy of Cytarabine with Different Regimens in Postremission Consolidation Therapy for Adult t(8;21) AML Patients: A Multicenter Retrospective Study in China

Abstract: Background: The survival of patients with acute myeloid leukemia (AML) with t(8;21) was reported to be shorter in China than in other countries. Patients: We analyzed the correlation between different cytarabine (Ara-c) regimens and outcome in 255 t(8;21) AML patients in China who received postremission consolidation chemotherapy only. Results: The 5-year overall survival (OS) of the high-dose Ara-c group (HDAC; 2≤ Ara-c ≤3 g/m2), intermediate-dose Ara-c group (MDAC; 1.0≤ Ara-c <2.0 g/m2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…However, the study of CALGB and JALSG AML201 was designed to compare HiDAC and SDAC (with [18] or without other chemotherapy [8,17]), not directly comparable to IDAC. While the retrospective study in AML with t (8;21) revealed the RFS and OS benefit of HiDAC over IDAC and SDAC [19], this study could not provide adequate information about this aspect because there were only five AML patients with favorable cytogenetic.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…However, the study of CALGB and JALSG AML201 was designed to compare HiDAC and SDAC (with [18] or without other chemotherapy [8,17]), not directly comparable to IDAC. While the retrospective study in AML with t (8;21) revealed the RFS and OS benefit of HiDAC over IDAC and SDAC [19], this study could not provide adequate information about this aspect because there were only five AML patients with favorable cytogenetic.…”
Section: Discussionmentioning
confidence: 85%
“…There were controversial issues regarding using IDAC as consolidation therapy in all AML patients. The analysis from CALGB study [17], Japan Adult Leukemia Study Group (JALSG) AML201 study [18], a retrospective study [19] and meta-analysis [11] supported the use of HiDAC in favorable risk cytogenetic patients including core-binding factor AML at least in terms of DFS or RFS. However, the study of CALGB and JALSG AML201 was designed to compare HiDAC and SDAC (with [18] or without other chemotherapy [8,17]), not directly comparable to IDAC.…”
Section: Discussionmentioning
confidence: 99%
“…In t(8;21) AML, additional cytogenetic abnormalities were detected in more than 70% of patients (15)(16)(17). The additional cytogenetic aberrations have substantial influence on prognosis and clinical outcomes (18)(19)(20)(21)(22). In our previous studies, t (8;21) AML patients with additional -Y could not benefit from HiDAC regimen (1.5-3 g/m 2 /12 h) (23), whereas for patients with additional -X, the HiDAC regimen was suitable (24).…”
Section: Introductionmentioning
confidence: 96%